Institute of presidency and term of its appointments in Ukraine and other countries of the world: comparatively legal analysis - Кохановський, Володимир Віталійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
History of becoming and development of institute of presidency, legal regulation and term of appointments,is analysed. Done comparatively legal analysis of institute of presidency of Ukraine and other countriesof the world.